Introduction to the Map of Indonesia using interactive animation design in multimedia-based elementary schools - Fathia; Mutammimul Ula; Riyadhul Fajri; Asmawi (Mulia International Journal in Science and Technical, 2018)
The use of technology automatically will provide convenience in the delivery of information. In this research, the use of technology can be done using animation to help and increase students' interest in participating in a more efficient learning process. This is done because some of the material learned is sometimes boring for students, especially in learning Geography science learning materials, even today students are less interested in studying Indonesian maps, because at this time the teacher only provides explanations through manual books and immovable drawings, in addition to lack of means and other information media such as pictures and encyclopedias supplied at school. From this problem, the author will research the design of interactive animations in the introduction of Indonesian state maps for multimedia-based school students. The software used in this research is Adobe Professional, Adobe Photoshop, and Wondershare Filmora. The method used in this study is a qualitative method, which is a research method that is more focused on the situation or phenomenon under investigation.